Regional and age‐related diversity of human mature oligodendrocytes. Issue 10 (23rd June 2022) - Yaqubi, Moein; Luo, Julia Xiao Xuan; Baig, Salma; Cui, Qiao‐Ling; Petrecca, Kevin; Desu, Haritha; Larochelle, Catherine; Afanasiev, Elia; Hall, Jeffery A.; Dudley, Roy; Srour, Myriam; Haglund, Lisbet; et al.
Abstract: Morphological and emerging molecular studies have provided evidence for heterogeneity within the oligodendrocyte population. To address the regional and age‐related heterogeneity of human mature oligodendrocytes (MOLs) we applied single‐cell RNA sequencing to cells isolated from cortical/subcortical, subventricular zone brain tissue samples, and thoracolumbar spinal cord samples. Unsupervised clustering of cells identified transcriptionally distinct MOL subpopulations across regions. Spinal cord MOLs, but not microglia, exhibited cell‐type‐specific upregulation of immune‐related markers compared to the other adult regions. SVZ MOLs showed an upregulation of select number of development‐linked transcription factors compared to other regions; however, pseudotime trajectory analyses did not identify a global developmental difference. Age‐related analysis of cortical/subcortical samples indicated that pediatric MOLs, especially from under age 5, retain higher expression of genes linked to development and to immune activity with pseudotime analysis favoring a distinct developmental stage. Our regional and age‐related studies indicate heterogeneity of MOL populations in the human CNS that may reflect developmental and environmental influences. Main Points: scRNA sequencing identified regionally distinct mature oligodendrocytes (OL) sub populations in the adult human CNS, including relative expression of immune markers. Pediatric OLs retain higher expression of genes linked to development and to immune activity.